Perancangan Teknis Pembangkit Listrik Tenaga Mikro Hidro Pada Irigasi Bendungan Sedau - Wili Ardianto; Agung Budi Muljono; Abdul Natsir (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2026)
Micro-Hydro Power Plant (MHPP) is a promising renewable energy solution to support electricity availability in rural areas with limited access to the national grid. This study was conducted in Sedau Village, Narmada District, West Lombok Regency, with the objective of planning an MHPP utilizing the irrigation channel of the Sedau Dam. The research method involved secondary data collection of river discharge records over the last ten years from the Nusa Tenggara I River Basin Agency, combined with primary field measurements of discharge and effective head. The analysis showed a dependable discharge (Q50) of 0.64 m³/s with an effective head of 11 m. The technical design included the construction of a forebay tank, penstock, selection of an S-type Kaplan turbine, mechanical transmission using a belt drive, and a three-phase induction generator Stamford N125G4. The calculations resulted in an installed capacity of 103.03 kW and an estimated annual energy production of 602.96 MWh. The implementation of this MHPP is expected to enhance local energy independence, reduce reliance on fossil fuels, and support regional economic development.